Resilience to cognitive fatigue between action gamers and non-gamers: insights into flexibility and task switching / Muhammad Hariz Mohd Nizam ... [et al.]. - Mohd Nizam, Muhammad Hariz; Mohd Pozi, Muhammad Ariff Munshir; Mohd Zaid, Amelia Natasya; Zianuddin, Muhammad Haiqal; Zani, Muhammad Isamuddin; Saiful Annur, Muhamad Safiq; Mohamed, Muhamad Noor (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Cognitive fatigue can impair task performance, yet action video games may bolster resilience by enhancing cognitive flexibility and task-switching skills. This study investigates the cognitive flexibility and task-switching performance of gamers compared to non-gamers and explores the impact of prolonged cognitive tasks on these abilities. Findings align with [1] report that habitual action video game players demonstrate superior cognitive abilities, such as spatial working memory and task-switching performance, compared to non-gamers, despite both groups showing cognitive fatigue under challenging conditions. Participants were categorized as action video game players (AVGPs, n = 18) or non-gamers (NGs, n = 18) based on self-reported gaming habits and questionnaires. To induce cognitive taxing, gamers were presented with a 45 minute Stroop Test while non-gamers observed a documentary entitled ‘A NASA Cassini Mission’. Cognitive flexibility and task-switching abilities were assessed using the Trail Making Test (TMT) and the Number-Letters Test (NLT). The TMT, a well-established tool sensitive to impairments in multiple cognitive domains, involves two parts: Part A assesses basic cognitive processing. At the same time, Part B requires additional cognitive flexibility and the ability to maintain a complex response set, which remains a subject of ongoing debate.